Skin Manifestations in Rheumatic Disease - Matucci-Cerinic, Marco; Furst, Daniel; Fiorentino, David; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Rheumatologic diseases are highly associated with clinical symptoms of the skin, nails, and mucosal membranes. This book provides the practicing rheumatologist with a rapid, easy to consult reference to help interpret the nature of these cutaneous lesions and then quickly decide upon the appropriate follow-up tests. Utilizing an abundance of informative photographs, it contains all of the essential information needed for early diagnosis and treatment. This comprehensive guide properly orients the practitioner within the challenging world of rheumatologic disorders of the skin and gives insight into when consultation with a dermatologist is advisable.
Part I: Presentation of Skin Manifestation -- Approach to Patients with Skin Manifestations -- Chilblain Lupus Erythematosus -- Erythema Nodosum -- Livedo Reticularis -- Malar Erythema -- Purpura -- Telangiectasias -- Ulceration in Rheumatic Disease -- Panniculitis -- Diagnosing Puffy Fingers in the Rheumatic Patient -- Part II: Methodology -- Capillaroscopy -- Use of Biopsy -- Part III: Inflammatory Joint Disease -- Skin Manifestations of Juvenile Idiopathic Arthritis -- Psoriasis and Psoriatic Arthritis -- Inflammatory Bowel Associated Spondyloarthropathy -- Nodules in Rheumatoid Arthritis -- Genital Involvement as a Result of Reactive Arthritis -- Keratoderma Blennorrhagica as a Result of Reactive Arthritis -- Parvovirus B19 Infection -- Rheumatic Fever -- Part IV: Connective Tissue Diseases -- Skin Manifestations of Localized Scleroderma (LS) -- Localized Scleroderma of the Face -- Skin Manifestations of Raynaud's Phenomenon -- Skin Manifestations of Systemic Sclerosis -- Skin Manifestations of Neonatal Lupus Erythematosus -- Skin Manifestations and Sjögren's Syndrome -- Skin Manifestations of Systemic Lupus Erythematosus -- Skin Manifestations in Dermatomyositis -- Stiff Skin Syndrome -- Nephrogenic Systemic Fibrosis -- Graft-versus-Host Disease (GvHD): Cutaneous Manifestations -- Scleromyxedema -- Eosinophilic Fasciitis -- Part V: Vasculitides -- Kawasaki Disease -- Dermatologic Manifestations of Granulomatosis with Polyangiitis (Wegener's Granulomatosis) -- Eosinophilic Granulomatosis with Polyangiitis (Churg-Strauss Syndrome) -- Polyarteritis Nodosa -- Skin Manifestations in Microscopic Polyangiitis -- Henoch Schönlein Purpura -- Skin Manifestations and Cryoglobulinemia -- Skin Manifestations in Giant Cell Arteritis -- Skin Manifestations of Behçet's Disease -- Familial Mediterranean Fever -- Cryopyrin-Associated Periodic Syndromes -- Part VI: Other Rheumatic Conditions -- Sarcoidosis -- Amyloidoses -- Hypertrophic Osteoarthropathy.
Keywords: Rheumatology; Internal medicine; Dermatology; Rheumatology; Internal Medicine; Dermatology